2007
DOI: 10.1007/s00270-006-0133-5
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Percutaneous Vertebroplasty Associated with Puncture or Cement Leakage

Abstract: Due to the minimally invasive character and excellent clinical outcome of percutaneous vertebroplasty (PVP), the procedure is being performed in greatly increasing numbers. While PVP has a low complication rate in general, severe complications can occur. We focus on the imaging appearance of complications of PVP associated with puncture or cement leakage--from harmless to life-threatening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 7 publications
1
44
0
3
Order By: Relevance
“…Although percutaneous vertebroplasty is considered a minimally invasive procedure, several dreadful complications are reported [1,7,25,27,33,34]. We retrospectively reviewed the medical records of patients who underwent vertebroplasty in our institutions and provided the different surgical methods used for patients who required revision surgery to deal with various complications after vertebroplasty failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although percutaneous vertebroplasty is considered a minimally invasive procedure, several dreadful complications are reported [1,7,25,27,33,34]. We retrospectively reviewed the medical records of patients who underwent vertebroplasty in our institutions and provided the different surgical methods used for patients who required revision surgery to deal with various complications after vertebroplasty failure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MRI should be performed for each patient to determine if repeated injection of bone cement will be effective. The reported incidence of cement extrusion is common, including leakage into the vertebral venous system, adjacent discs, lateral or anterior vertebrae, and leakage leading to pulmonary embolism [1,7,23,36]. Most authors have described that cement extrusion presented as asymptomatic in the majority of cases and could be treated conservatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous vertebroplasty was first described by Galibert et al in 1987 and has been performed to treated painful vertebral compression fracture secondary to osteoporosis and neoplasms [4]. Is reported that the complications rate associated with PVP is 1-3% [28], including pulmonary cement embolism, cement extravasation with subsequent cord or roots compression associated to neurologic disorders, and allergic reactions [42]. In addition some authors have indicated that there could be an increased risk of collapse in vertebral bodies contiguous to the level treated with PVP [7,28,43].…”
Section: Sandwich Vertebra and Prophylactic Pvpmentioning
confidence: 99%
“…ercutaneous vertebroplasty is a relatively noninvasive, low-risk procedure 1,2 that provides immediate and durable pain relief [3][4][5] and improved function 6,7 to patients with painful vertebral compression fractures (VCF).…”
mentioning
confidence: 99%